DEVELOPMENT AND PSYCHOMETRIC PROPERTIES OF THE COMMUNITY INTEGRATION SCALE OF ADULTS WITH PSYCHIATRIC DISORDERS - Cabral, Joana Moura; Carvalho, Célia Maria Oliveira Barreto; da Motta, Carolina Dall’Antonia; da Silva, Osvaldo Dias Lopes (European Scientific Journal, ESJ, 2014)
The goal of the current study was to develop and validate the Community Integration Scale for Adults with Psychiatric Problems (CISAPP), based on a multidimensional model of community integration. The three-dimensional structure (including physical, psychological, and social dimensions) and validity of CIS-APP was studied in a sample of 183 psychiatric patients from the Azores Islands-Portugal. Confirmatory Factor Analysis has led to the choice of a two-factor with a second order factor solution. Results showed that the CIS-APP is a measure with good psychometric properties, with very good internal consistency and validity, and with relevant applicability in both clinical and research settings. Furthermore, the current outcomes have brought relevant information concerning the refinement of the theoretical community integration model that underlies the scale’s development.